A New Fast Algorithm for Constrained Four-Directional Total Variation Image Denoising Problem. (23rd February 2015) - Liao, Fan; Coatrieux, Jean Louis; Wu, Jiasong; Shu, Huazhong
Abstract : A new four-directional total variation (4-TV) model, applicable to isotropic and anisotropic TV functions, is proposed for image denoising. A dual based fast gradient projection algorithm for the constrained 4-TV image denoising problem is also reported which combines the well-known gradient projection and the fast gradient projection methods. Experimental results show that this model provides in most cases a better signal to noise ratio when compared to previous models like the reference TV, the total generalized variation, and the nonlocal total variation.